2007
DOI: 10.1111/j.1462-5822.2007.00992.x
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms ofSalmonellaentry into host cells

Abstract: SummarySalmonella enterica is an enteric bacterial pathogen that causes a variety of food and water-borne diseases ranging from gastroenteritis to typhoid fever. Ingested bacteria colonize the intestinal epithelium by triggering their own phagocytosis, using a sophisticated array of effector proteins that are injected into the host cell cytoplasm through a type III secretion apparatus. The synergistic action of these secreted effectors leads to a dramatic reorganization of the host actin cytoskeleton, resultin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
83
0
2

Year Published

2009
2009
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 108 publications
(86 citation statements)
references
References 69 publications
1
83
0
2
Order By: Relevance
“…Salmonella can thus infect a wide range of tissues and cell types. The best-characterized Salmonella invasion process requires a type three secretion system (T3SS-1) encoded by Salmonella pathogenicity island 1 (SPI-1) (Ly & Casanova, 2007). In vivo studies with the Salmonella Dublin and Salmonella Typhimurium serovars have demonstrated that T3SS-1 is essential for intestinal colonization and is required to induce enterocolitis in bovine, rabbit and murine models (Wallis & Galyov, 2000).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Salmonella can thus infect a wide range of tissues and cell types. The best-characterized Salmonella invasion process requires a type three secretion system (T3SS-1) encoded by Salmonella pathogenicity island 1 (SPI-1) (Ly & Casanova, 2007). In vivo studies with the Salmonella Dublin and Salmonella Typhimurium serovars have demonstrated that T3SS-1 is essential for intestinal colonization and is required to induce enterocolitis in bovine, rabbit and murine models (Wallis & Galyov, 2000).…”
Section: Introductionmentioning
confidence: 99%
“…cytoplasm to manipulate the cell cytoskeleton, allowing bacterial internalization (Ly & Casanova, 2007). This entry process is referred to as the Trigger entry mechanism and has mainly been studied with epithelial cells.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…SipC interacts with SipB to form an extracellular complex following their secretion through the SPI-1 T3SS, and they are thought to assemble into a plasma membrane-integral structure (translocon) that mediates effector delivery and facilitates effector transport (Hayward & Koronakis, 1999;Ly & Casanova, 2007;Scherer et al, 2000). In addition to its role as a component of the translocon, SipC is an actin-binding protein that nucleates actin filament formation in vitro and contributes to Salmonella-induced inflammation in vivo (Chang et al, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…Both of these T3SSs are required at different stages of infection. During non-phagocytic cell invasion, the SPI-1 T3SS is activated and translocates several effector proteins into host cells to induce actin polymerization and membrane ruffling (Ly & Casanova, 2007), while the SPI-2 T3SS is important for intracellular survival and replication within macrophages (Ochman & Groisman, 1996). The SPI-1-associated protein InvE is essential for bacterial internalization and controls the secretion of translocases (SipB, SipC and SipD) of the SPI-1 T3SS (Ginocchio et al, 1992;Kubori & Galán, 2002).…”
Section: Introductionmentioning
confidence: 99%